Silencing and Breaking the Silence: Resisting Patriarchy in Brajaki’s “Annapurna’s Feast” and Thakuri’s “War” - Adhikari, Nirjala (SCHOLARS: Journal of Arts & Humanities, 2021)
The aim of this paper is to analyse Manu Brajaki’s story “Annapurna’s Feast” and Maya Thakuri’s “War,” using the resistance theory. It explores the nature of resistance and its significance presented in the stories. The paper argues that both female protagonists of the stories resist injustice happened in their life due to their gendered identity as women, but the way they resist is different: one directly shows the courage and declares to fight against it whereas another silently inherits all the patriarchal value although her silence speaks out loud and gives agency to her voice. To elucidate this statement, Hollander and Rachel L. Einwohner’s concepts on resistance is used. Both stories depict the life of the housewives who are victimized due to existing patriarchal values. The female protagonist of Brajaki seems so resilient whereas Thakuri’s protagonist directly speaks out for the injustice. Both stories present the female protagonists’ silence and courage to speak out as their ways to resist and expose their difficulties to speak out.